2019
DOI: 10.1111/ipd.12466
|View full text |Cite
|
Sign up to set email alerts
|

Is dental trauma more prevalent in maltreated children? A comparative Study in Southern Brazil

Abstract: Background Although a high prevalence of head and neck trauma has been reported in maltreated children and adolescents, most of these studies focused on record‐based analyses, and only a few used control groups. Aim To assess the presence of dental trauma in maltreated children in comparison with children without a history of maltreatment. Design A cross‐sectional study with 68 maltreated children and 204 age, sex‐, and school‐matched control participants was conducted in Pelotas, a Southern Brazilian city. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 26 publications
(76 reference statements)
0
16
0
1
Order By: Relevance
“…Although neglect is the most common and reported type of maltreatment in some countries 37,38 , the present study dealt only with child physical abuse, in contrast to other studies. A paediatric dentist can readily diagnose child physical abuse during a routine examination, as well as management of a traumatic dental injury 8,20 . The present study had limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although neglect is the most common and reported type of maltreatment in some countries 37,38 , the present study dealt only with child physical abuse, in contrast to other studies. A paediatric dentist can readily diagnose child physical abuse during a routine examination, as well as management of a traumatic dental injury 8,20 . The present study had limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Injury in a child resulting from a physical assault is probably the most common type of abuse that paediatric dentists could encounter. Studies have shown that the head and orofacial region are common sites of trauma from child abuse. Paediatric dentists can provide valuable information and assistance to physicians about orodental signs of child physical abuse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the 17 primary studies presented an observational study design and were conducted in four different settings: hospitals, 9,16,[34][35][36][37][38][39][40] the Institute of Forensic Medicine, [41][42][43][44][45][46] police records, 13 and social services. 47,48 Three out of the six studies conducted in the Institutes of Forensic Medicine were performed on cadavers and included cases of homicides. [44][45][46] The majority of the included studies were indirect and assessed prevalence data through retrospective analysis of records available in institutional databases.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%